The Protective Effects of Bevacizumab in Bleomycin-Induced Experimental Scleroderma - Koca, S.S.; Özgen, M.; Daǧli, A.F.; Gözel, N.; Özercan, I.H.; ISIK, A. (Wroclaw University of Medicine, 2016)
Background: The capillary networks are less dense and have irregular structures in scleroderma. These abnormalities result in lower capillary blood flow causing severe tissue hypoxia, which is a major stimulus for angiogenesis. However, current knowledge about compensatory angiogenesis is ambiguous in scleroderma. Bevacizumab is an inhibitor of vascular endothelial growth factor (VEGF). Objectives: The aim of the present study is to evaluate the protective effects of bevacizumab in bleomycin (BLM)-induced dermal fibrosis. Material and Methods: This study involved 4 groups of Balb/c mice (n = 10 per group). Mice in the control group received 100 μL/day of phosphate-buffered saline (PBS) subcutaneously, while the other 3 groups were given 100 μg/day of BLM (dissolved in 100 μL PBS) subcutaneously, for 4 weeks. Mice in BLM-treated 3rd and 4th groups also received bevacizumab (1 or 5 mg/kg twice a week, intraperitoneally). At the end of the fourth week, all mice were sacrificed and blood and tissue samples were obtained. Results. The BLM applications increased the dermal thicknesses, tissue hydroxyproline contents, and á-smooth muscle actin-positive (α-SMA+) cell counts, and led to histopathologically prominent dermal fibrosis. The bevacizumab treatments decreased the tissue hydroxyproline contents and dermal thicknesses, and these improvements were more prominent at doses by which á-SMA+ cell counts were markedly decreased, in the BLM-injected mice. Conclusions: In our study, inhibition of VEGF with bevacizumab treatments prevented the BLM-induced dermal fibrosis suggesting that VEGF expression contributes to the pathogenesis of scleroderma. © Copyright by Wroclaw Medical University.
Keywords: Bevacizumab; Dermal Fibrosis; Scleroderma; VEGF